The Sensitivity and Specificity of Rotational Thromboelastometry (ROTEM) to Detect Coagulopathy During Moderate and Severe Postpartum Hemorrhage: A Prospective Observational Study. Issue 4 (21st December 2022) - Bell, S.F.; Roberts, T.C.D.; Freyer Martins Pereira, J.; De Lloyd, L.; Amir, Z.; James, D.; Jenkins, P.V.; Collis, R.E.; Collins, P.W.
Abstract : ( Int J Obstet Anes . 2022;49:103238) Viscoelastometric hemostatic assays, such as rotational thromboelastometry (ROTEM), offer rapid, point-of-care identification of coagulopathy during postpartum hemorrhage (PPH). Previous studies investigating the use of ROTEM have used a Delta ROTEM device. This study investigates the use of the ROTEM Sigma device, identifying the sensitivity, specificity, and positive or negative predictive values in patients with PPH.